Exosomal miR-4800-3p Aggravates the Progression of Hepatocellular Carcinoma via Regulating the Hippo Signaling Pathway by Targeting STK25 - Lin, Haoming; Peng, Jicai; Zhu, Taifeng; Xiong, Meihong; Zhang, Rui; Lei, Liming (Frontiers in Oncology, 2022)
Background: Emerging evidence has shown that exosome miRNAs regulate the development of hepatocellular carcinoma (HCC). Here, the influences of miR-4800-3p on the progression of HCC were explored. Materials and Methods: The expression of miR-4800-3p in the exosome derived by TGF-β1-treated HCC cells and the serum exosome isolated from HCC patients were identified by real-time PCR. The effects of TGF-β1 and the influences of Huh7-secreted exosomes, and the effects of miR-4800-3p combined with/without STK25 on cell functions were explored using the EdU assay cloning experiments, wound healing assay and transwell assay. The corresponding molecular mechanisms were further detected using western blot and real-time PCR assays. The combination of miR-4800-3p and STK25 was verified by the dual-luciferase and RNA pulldown assays. The influences of miR-4800-3p on the growth and epithelial-mesenchymal transformation (EMT) of implanted tumors were tested in vivo and further confirmed by Western blot. Results: The miR-4800-3p expression was highly expressed in both exosomes derived by TGF-β1-treated HCC cells and serum exosomes of HCC patients. In the cases of treatment with both Huh7-derived exosomes, the level of miR-4800-3p expression was highest, and the treatment of TGF-β1 could greatly promote the proliferation, stemness, migration and invasion of HCC cells via up-regulating the markers of stemness and EMT, including CD44, CD133, OCT4, N-cadherin, E-cadherin and ZO-1. Similar results could be obtained when miR-4800-3p was overexpressed in HCC cells. Furthermore, down-regulation of STK25 expression, a direct target gene of miR-4800-3p, could greatly rescue the malignant biological behaviors aggravated by overexpression of miR-4800-3p. This was achieved by suppressing the expression of CD44, CD133, OCT4, N-cadherin and PCNA and activating the Hippo pathway while increasing E-cadherin and ZO-1. Similar results were also obtained in vivo that knockdown of miR-4800-3p expression suppressed tumor growth induced by Huh7-derived exosomes by mediating the EMT markers and the Hippo signaling pathway. Conclusion: Exosomal miR-4800-3p could accelerate HCC development by regulating the Hippo signal by targeting STK25, which could be used as a new therapeutic target for HCC treatment.